2012 IEEE International Conference on Communications (ICC) 2012
DOI: 10.1109/icc.2012.6364043
|View full text |Cite
|
Sign up to set email alerts
|

The performance loss of unilateral interference cancellation

Abstract: Abstract-We tackle the problem of determining the beamforming and combining weights in a network of interfering multiple-input multiple-output (MIMO) links. We classify any strategy for computing these weights as either unilateral or bilateral. A unilateral strategy is one for which the responsibility of cancelling interference from one node to another is preassigned to lie solely with only one of the two nodes, so that the other node is free to ignore the interference. Many existing strategies for managing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However, it guarantees that local solutions can be pieced together to form a valid global solution, and it is extremely fast because it is a one-step (noniterative) approach. In [8], it was shown that, using iterative solution techniques, piecing local solutions into a global solution can be done successfully even when cycles exist in the interference cancellation assignments. Therefore, we consider a unilateral interference cancellation assignment to be feasible whenever the local systems of equations are all solvable.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it guarantees that local solutions can be pieced together to form a valid global solution, and it is extremely fast because it is a one-step (noniterative) approach. In [8], it was shown that, using iterative solution techniques, piecing local solutions into a global solution can be done successfully even when cycles exist in the interference cancellation assignments. Therefore, we consider a unilateral interference cancellation assignment to be feasible whenever the local systems of equations are all solvable.…”
Section: Related Workmentioning
confidence: 99%
“…However, in the networking literature, it is more commonly assumed that interference cancellation is assigned to either the transmitter or the receiver, but not both [3], [4], [17], [23], [29]- [31], [35]. In [8], Cortés-Peña et al compared these two approaches, referring to the former as bilateral interference cancellation and the latter as unilateral interference cancellation. In this paper, we assume unilateral interference cancellation.…”
Section: A Interference Cancellation With Mimomentioning
confidence: 99%
See 3 more Smart Citations